Lawsuit and Traumatic Brain Injury: The Relationship Between Long-Lasting Sequelae and Financial Compensation in Litigants. Results From the PariS-TBI Study - Bayen, Eléonore; Ruet, Alexis; Jourdan, Claire; Ghout, Idir; Meaude, Layide; Pradat-Diehl, Pascale; Nelson, Gaëlle; Vallat-Azouvi, Claire; Charanton, James; Aegerter, Philippe; Azouvi, Philippe (Frontiers in Neurology, 2019)
ABSTRACT Purpose: People with traumatic brain injury are frequently involved in a litigation because another person was at fault for causing the accident. A compensation amount will often be settled to compensate the victim for the past, present, future damages and losses suffered. We report descriptive data about the full and final personal compensation amount and investigated its association with patient’s outcomes. Methods: We used a longitudinal prospective study of severe TBI patients injured in 2005-2007 (PariS-TBI). Questions regarding involvement in a litigation were asked concurrently with 4 and 8-year outcomes. Results: Among 160 participants assessed 4 and/or 8 years post-injury, a total of 67 persons declared being involved in a litigation, among which 38 people reported a compensation amount of a mean €292653 (standard deviation=436334; interquartile 25-50-75=37000-100000-500000; minimum=1500-maximum=2000000). A higher compensation amount was associated with more severe disability and cognitive impairment in patients, and with more informal care time provided by caregivers. However, no significant association related to patient’s gender, age, years of education, motor/balance impairment, return to work status, mood and related to caregiver’s subjective burden was found. Conclusion: Financial compensation was related to victims’ long-term severity of impairment, although some extreme cases with severe disability were granted very poor compensation.